Kemampuan Prediksi Aliran Kas Operasi Utama dan Bukan Utama: Studi Empiris pada Perusahaan Manufaktur di Indonesia - Hadri Kusuma (Universitas Islam Indonesia, 2006)
The issue of separating core and non-core cash flow components of financial reporting is controversial among financial analysts and accounting standard setters. This paper examines the relevance of key attributes of the financial statement and the role of those components in predicting the future cash flow. Overall this study supports the relevancy and predictability cash flow statements. The study also supports the need of financial analysts and standard setters to separate the components of core and non-core cash flows from operations.Keyword: core cash flow, net income, accrual, relevancy, predictable, accounting standard.